An investigation into a foldable freight container for shipping industry - Sim, Daniel Ching Leong. (2009)
This work proposes a foldable concept incorporating one side of the freight container to be hinged to the base and the other side hinged to the top, forming a “L” like foldable structure, hence the name Double L foldable freight container. This design of foldable freight container is proposed to address the issues of trade imbalance between countries or regions due to presence of vast number of empty freight containers.